Management information systems managing the digital firm - Laudon, Kenneth C. 1944-; Laudon, Jane Price (Pearson, 2022)
Thistitle is a Pearson Global Edition. The Editorial team at Pearson has workedclosely with educators around the world to include content which is especiallyrelevant to students outside the United States. For introductory courses in IS (information systems)and MIS (management information systems). The authoritative, case-based study of IS in business today Management Information Systems: Managing the Digital Firm providesthe most comprehensive overview of information systems used by business firms today,while drawing connections between MIS and business performance. The Laudons areknown for